Integrating Management and Marketing Strategies in Organic Farming: A Topic Modeling Analysis of Sustainable Development and Entrepreneurship - Chiangnangam, Sumana; Manorom, Paiboon; Chansanam, Wirapong (International Review of Management and Marketing, 2024)
Integrating management and marketing with organic farming practices is crucial for the sustainable development of this growing sector. As organic farming products are popular among health-conscious consumers, agricultural entrepreneurs increasingly use innovative business strategies to meet the rising demand. The successful alignment of business and economic principles with organic agriculture enhances value creation and promotes long- term sustainability. Entrepreneurs must focus on strategic networking across production, processing, and marketing to capitalize on these opportunities fully. Despite its growth, the organic agriculture sector still faces challenges that require comprehensive research to develop effective strategies for advancing the industry. This study addresses the intersection of organic agriculture, entrepreneurship, and business strategy by utilizing topic modeling techniques to analyze bibliographic data from 4327 articles published between 1946 and 2023 in the Scopus database. Using Latent Dirichlet Allocation (LDA) topic modeling, five key themes were identified: (1) Soil for organic agriculture, (2) Environment and organic agriculture, (3) Agriculture business, (4) Organic production, and (5) The use of organic substances. With a connection value of 0.419, the topic modeling effectively grouped relevant themes, offering valuable insights into the role of management and marketing in organic farming. These findings provide a solid foundation for future research and innovation, enabling entrepreneurs, researchers, and farmers to align their practices with evolving market trends better, thus fostering the continued growth of organic agriculture.